Medidas laborales durante emergencia nacional sanitaria por covid-19 - Sierra Huezo, Claudette María (2026)
This article presents a chronological description of the labor measures taken by the Honduran Government through competent state institutions to mitigate the economic impact on the country, resulting from the total confinement intended to prevent the spread of the Covid-19 virus, as ordered by the Council of State Secretaries by Executive Decree 021-2020, dated Monday March 15, 2020.